Perlindungan Konsumen dalam Transaksi Pemesana Hotel Melalui Platform Digital: Analisis Normatif terhadap Kasus Penolakan Layanan oleh Pihak Hotel Indonesia Pekalongan - Joshua Walker Siregar; Thea Farina; Nuraliah Ali; Joanita Jalianery (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze consumer protection in hotel booking transactions through digital platforms, focusing on a service refusal case involving a hotel in Pekalongan, Indonesia. The research uses a normative approach by examining relevant regulations, including the Consumer Protection Act and provisions governing the rights and obligations of consumers and business actors in digital transactions. The findings show that hotels must act in good faith, provide honest, proper and non-discriminatory services and deliver accurate information. Both the hotel and Traveloka are responsible for consumer losses through full refunds. This study contributes to developing more effective consumer protection policies.